1995
DOI: 10.1177/096120339500400111
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA class II antigens and primary antiphospholipid syndrome from the South of Spain

Abstract: Recent studies have suggested an association between primary antiphospholipid syndrome (PAPS), antiphospholipid antibodies and some major histocompatibility complex (MHC) antigens. We have studied the relationship between MHC class II antigens and PAPS in 19 patients from the south of Spain. Univariant analysis showed an association between PAPS and HLA-DQ7 (47% vs 25%l P = 0.3), DR4 (32% vs 16%; P = 0.08) and DQ3 (63% vs 39%; P = 0.04). However, multivariant analysis confirmed the association with DQ7 (RR = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…In a study of 13 patients with the primary APS, HLA-DR4 and DRw53 were more frequently found, but no correction was made for multiple comparisons [24]. The data confirmed in a population from Spain [25] and Canada [7]. Studies of HLA alleles in patients with conventianal aCL showed increased frequencies of HLA DR4 [26] or DR7 [25,27] in SLE population.…”
Section: Genes Associated With Antiphospholipid Syndromesupporting
confidence: 57%
See 1 more Smart Citation
“…In a study of 13 patients with the primary APS, HLA-DR4 and DRw53 were more frequently found, but no correction was made for multiple comparisons [24]. The data confirmed in a population from Spain [25] and Canada [7]. Studies of HLA alleles in patients with conventianal aCL showed increased frequencies of HLA DR4 [26] or DR7 [25,27] in SLE population.…”
Section: Genes Associated With Antiphospholipid Syndromesupporting
confidence: 57%
“…The data confirmed in a population from Spain [25] and Canada [7]. Studies of HLA alleles in patients with conventianal aCL showed increased frequencies of HLA DR4 [26] or DR7 [25,27] in SLE population. DR7 was also increased in Mexican patients with aCL [28].…”
supporting
confidence: 65%
“…Alarcon-Segovia and Granados have previously reported an increase in DR7 in Mexican patients with PAPS [11]. HLA-DR7 is the most frequent allele in the Spanish population [12], and in PAPS patients from the south of Spain, HLA-DQ7 antigen confers the highest relative risk for PAPS, followed by DRw53, without statistically significant association between the histocompatibility class I and II antigens and the presence of aCL or LA [13]. In the family reported here, the propositus, with cerebrovascular symptoms, LR, and skin biopsy, had confirmed SS [14]; her father manifested PAPS.…”
Section: Discussionmentioning
confidence: 95%
“…Identification of genes involved in familial disease will shed light on pathways involved in disease expression, and with time, should lead to more specific and hopefully less toxic therapies. LAC DR5, DRw52b, DQB1*0301 (DQw7), or DQB1*0302 (DQw8) [79] aCL antibody DR7 [72,78,87] DR4 [74] Anti-phosphatidylserine/ DQB1*0301/4;DQA1*0301/2;DRB prothrombin antibodies 1*04 [81] Anti-β2-glycoprotein DQB1*0604/5/6/7/9; I antibody DQA1*0102; DRB1*1302 and DQB1*0303 [81,82] …”
Section: Discussionmentioning
confidence: 99%